POTENSI SUMBER DAYA DAERAH DAN KESEJAHTERAAN KELUARGA TKI - Nuraini, Ida; Rochminarni, Arfida Boedi (Pusat Pengkajian Ekonomi dan Kebijakan Publik, 2013)
The objective of this study was to investigate the local resource potential and migrant workers’ family welfare. The data were analyzed through Structural Equation MODELING (sem) or so-called Linear Structural Equation (LISREL) to measure the connection of resources in the workers’ origins and poverty. The results show that both human dan natural resources do not significantly affect the walfare of migrant workers’ families. Hence, the Local Government (Regency) is expected to increase financeial resources such as banking institutions, cooperatives, savings and loan institutions, finance and so on, besides increasing the number of physical resources such as markets and roads.